2007
DOI: 10.1095/biolreprod.106.058230
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF) 2 Stimulates Steroidogenesis and Mitosis of Bovine Granulosa Cells Through the IGF1 Receptor: Role of Follicle-Stimulating Hormone and IGF2 Receptor1

Abstract: Little is known regarding the role of insulin-like growth factor 2 (IGF2) and the regulation of the IGF2 receptor (IGF2R) during follicular development. Granulosa cells were collected from small (1-5 mm) and large (8-22 mm) bovine follicles and were treated with IGF2 for 1-2 days in serum-free medium, and steroid production, cell proliferation, specific 125 I-IGF2 binding, and gene expression were quantified. IGF2 increased both estradiol and progesterone production by granulosa cells, and cells from large fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 65 publications
5
105
0
Order By: Relevance
“…More recently, IGF2 has also been shown to stimulate estradiol and progesterone secretion by granulosa cells (Spicer and Aad, 2007). There is also evidence of insulin/IGFs influencing steroidogenesis in other mammalian glands such as the adrenals.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, IGF2 has also been shown to stimulate estradiol and progesterone secretion by granulosa cells (Spicer and Aad, 2007). There is also evidence of insulin/IGFs influencing steroidogenesis in other mammalian glands such as the adrenals.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the role of IGF2R in regulating IGF2 bioavailability in the follicle, the present results suggest that the ability of IGF2 to activate IGF1R may be impaired in transitional follicles relative to ovulatory follicles. Although the effects of IGF1 injection on IGF2R were not determined in this study, IGF2R expression in bovine granulosa cells has been shown to decrease in response to IGF1 (Spicer & Aad 2007).…”
Section: Discussionmentioning
confidence: 80%
“…The expression levels of IGF2R, FSHR and LHCGR in granulosa cells were determined because the responses of follicular cells to IGF1 may depend, at least in part, on their concurrent responsiveness to IGF2 (Spicer & Aad 2007) and gonadotrophins (Glister et al 2001). IGF2 is naturally produced in equine follicular cells , Watson et al 2004a) and IGF2 expression is lower during the transitional period than during the ovulatory season (Watson et al 2004a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations